PEMILIHAN MODA PERJALANAN MENUJU KAWASAN OBYEK WISATA MENARA KUDUS MENGGUNAKAN MODEL LOGIT BINER - Nurul Hidayati; Emir Al Hasan; Zilhardi Idris; Gotot Slamet Mulyono (LPPM, 2023)
The trip to the Menara Kudus tourist area can be reached using various vehicles. The availability of various choices of transportation modes has resulted in an increase in traffic flow around the area. This study aims to identify the characteristics, factors that influence respondents in choosing a mode and analyze the modeling. The primary data needed is the characteristics of the respondent and the trips made, as well as the modal facilities used. Other data used is the location map and the number of tourists. Questionnaires were distributed online and obtained by 340 respondents. The analysis was carried out using a binary logic model using the parameter number of voters for each mode and costs based on the recapitulation of questionnaire data. The results of the analysis obtained that the majority of respondents used motorbikes and cars, were female, aged 17-25 years and had student status. Other results show that the majority of samples come from Gebog District, Kudus Regency, which has a travel time of less than 25 minutes and is 5-10 km away. Factors that influence the choice of mode are convenience and comfort. The results of the difference logic modeling show that there is a discrepancy between the logic and the facts. Logically, if the cost difference between the two modes gets smaller (cars are cheaper), then the chances of choosing a motorcycle will decrease. However, the results obtained are contrary to these conditions. This discrepancy also occurs in logic ratio modeling. Logically, if the cost ratio of the two modes is less than one (motorcycles are cheaper), then the probability of choosing a motorcycle will increase. However, the results obtained actually decreased the chances. This happened due to different consideration factors between respondents who came from near and far away from Kudus Regency.